2021
DOI: 10.1097/ju.0000000000001763
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Prostate Specific Antigen Screening and Referral to Urology in a Large, Integrated Health Care System: A Retrospective Cohort Study

Abstract: Purpose: Contemporary trends and racial disparities in prostate cancer screening and referral to urology for prostate cancer risk are not well characterized, despite consensus that Black men are at higher risk for poor prostate cancer outcomes. The objective of this study was to characterize current racial disparities in prostate cancer screening and referral from primary care to urology for prostate cancer concern within our large, integrated health care system. Materials and Methods: This retrospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“… 6 , 7 In contrast, Black men with prostate cancer in the US consistently have disparities in SDOH, such as decreased access to health care, reduced prostate-specific antigen screening, economic instability, receipt of less guideline-concordant cancer care, greater number of comorbid conditions, lower likelihood of treatment of comorbid conditions, reduced curative-intent treatment, and reduced access to high-volume centers, all of which reflect SDOH that can be associated with health outcomes. 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 7 In contrast, Black men with prostate cancer in the US consistently have disparities in SDOH, such as decreased access to health care, reduced prostate-specific antigen screening, economic instability, receipt of less guideline-concordant cancer care, greater number of comorbid conditions, lower likelihood of treatment of comorbid conditions, reduced curative-intent treatment, and reduced access to high-volume centers, all of which reflect SDOH that can be associated with health outcomes. 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…6,7 In contrast, Black men with prostate cancer in the US consistently have disparities in SDOH, such as decreased access to health care, reduced prostate-specific antigen screening, economic instability, receipt of less guideline-concordant cancer care, greater number of comorbid conditions, lower likelihood of treatment of comorbid conditions, reduced curative-intent treatment, and reduced access to highvolume centers, all of which reflect SDOH that can be associated with health outcomes. [8][9][10][11][12][13] There continues to be considerable heterogeneity in the extent, and even existence, of racial disparities in prostate cancer survival outcomes in the literature. Large registry studies have found profound racial disparities in prostate cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the medical literature consistently supports the concerning reality that African American men are insufficiently screened for both BPH and prostate cancer [29]. Consistent with other healthcare issues, African American men are more likely to be disproportionately impacted by insufficient healthcare literacy [30][31][32].…”
Section: Screening Literacy and Community Interventionmentioning
confidence: 98%
“…It contains seven questions related to BPH symptoms and one question related to the patient's perceived quality of life. BPH symptom severity is proportionate to the IPSS score, which ranges from 0 to 35 and categorizes symptoms as mild (1-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), or severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The IPSS survey is widely used in Urology and the AUA also encourages its use in primary care settings.…”
Section: Screening Literacy and Community Interventionmentioning
confidence: 99%
“…In the United States (US), Black men are 1.75 times more likely to be diagnosed with and twice as likely to die of prostate cancer (PC) than White men [1]. Disparities in the incidence and mortality rate of PC and in screening and access to treatment between Black and White men are well documented [1][2][3][4][5]. The racial disparities in PC are likely multifactorial, including social, cultural, and biological determinants of health [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%